Interleukin-1-Beta and Dyslipidemic Syndrome as Major Risk Factors for Thrombotic Complications in Type 2 Diabetes Mellitus - Oana Bădulescu; Codruţa Bădescu; Manuela Ciocoiu; Magda Bădescu (Hindawi Limited, 2013)
Diabetes mellitus (DM) is a complex disease characterized by chronic hyperglycemia, a known risk factor for accelerated atherosclerosis and vascular disease. The aim of this study was to show that the connection between DM and other risk factors, such as dyslipidemia, inflammatory phenomena, or the development of certain vascular injuries, leads to a high frequency of thrombotic events in diabetic patients compared to the nondiabetic population. The study included one hundred eighty patients divided in the following groups: diabetic without ischemic cardiopathy-related disorders (DM), diabetic with clinical or off-clinical (electrocardiogram, cardiac ultrasound) ischemic cardiopathy-related disorders (DM + IC), and nondiabetic with ischemic cardiopathy-related disorders (IC). We investigated the following parameters: von Willebrand Factor, HDL-cholesterol, LDL-cholesterol, interleukin-1-beta, protein C, and plasminogen activator inhibitor type 1. The results achieved in our study have revealed the highest thrombotic risk among the groups of diabetic patients, which is in direct correlation with the high values of interleukin-1-beta and the modifications of lipid parameters, acknowledging the data in the literature, according to which hyperglycemia alters endothelial functions directly and indirectly by synthesis of growth factors and cytokines and generates metabolic disorders which would explain the high risk for thrombotic events.